Ibuprofen Inhibits Overexpression of Tumor-Related RAC1B through SRSF1 - Gonçalves, Vânia (2021)
The serrated pathway to colorectal tumor formation involves oncogenic mutations in the BRAF gene, which are sufficient for initiation of hyperplastic growth but not for tumor progression [1]. A previous analysis of colorectal tumors revealed that overexpression of splice variant RAC1B occurs in around 80% of tumors with mutant BRAF and both events proved to cooperate in tumor cell survival [2]. Patients with inflamed human colonic mucosa also have increased expression of RAC1B as well as mice with experimentally induced colitis [3]. The increase of RAC1B in the mouse model was specifically prevented by the nonsteroidal anti-inflammatory drug ibuprofen [3]. The objective of our study is to understand the molecular regulation of RAC1B alternative splicing event and how it contributes to tumorigenesis. HT29 colorectal cell line was used as model to test several signaling pathways after 48h of treatment with ibuprofen. For this we analyzed the proteins of interest by Western Blot and the transcript levels by RT-PCR. Mechanistic studies in cultured HT29 colorectal tumor cells revealed that ibuprofen inhibited RAC1B expression in a cyclooxygenase inhibition–independent manner and targets directly the alternative splicing event [3]. Here, we provide evidence that ibuprofen leads to a protein kinase dependent decrease in expression of SRSF1, a splicing factor that we previously identified to promote RAC1B alternative splicing. Together, our results suggest that stromal cues, namely, inflammation, can trigger changes in RAC1B expression in the colon and identify ibuprofen as a highly specific and efficient inhibitor of RAC1B overexpression in colorectal tumors. Our data identify an additional cyclooxygenase–independent action of ibuprofen and suggest it may be beneficial in the treatment of patients with the subtype of BRAF-mutated serrated colorectal tumors. References [1] Velho S, Moutinho C, Cirnes L, Albuquerque C, Hamelin R, Schmitt F, Carneiro F, Oliveira C, and Seruca R (2008). BRAF, KRAS and PIK3CA mutations in colorectal serrated polyps and cancer: primary or secondary genetic events in colorectal carcinogenesis? BMC Cancer 8, 255. [2] Matos P, Oliveira C, Velho S, Gonçalves V, da Costa LT, Moyer MP, Seruca R, and Jordan P (2008). B-Raf V600E cooperates with alternative spliced Rac1b to sustain colorectal cancer cell survival. Gastroenterology 135, 899–906. [3] Matos P, Kotelevets L, Goncalves V, Henriques AF, Henriques A, Zerbib P, Moyer MP, Chastre E, Jordan P (2013). Ibuprofen inhibits colitis-induced overexpression of tumor-related Rac1b. Neoplasia 15(1):102-11. Acknowledgements Funding Support: grant UID/MULTI/04046/2019, SFRH/BD/109162/2015 and PTDC/BIA-MOL/28386/2017 from FCT